2022
DOI: 10.1161/circulationaha.122.057444
|View full text |Cite
|
Sign up to set email alerts
|

Management of Atrial Fibrillation Across the Spectrum of Heart Failure With Preserved and Reduced Ejection Fraction

Abstract: Atrial fibrillation (AF) is the most common arrhythmia among patients with heart failure (HF), and HF is the most common cause of death for patients presenting with clinical AF. AF is frequently associated with pathological atrial myocardial dysfunction and remodeling, a triad that has been called atrial myopathy. AF can be the cause or consequence of clinical HF, and the directionality varies between individual patients and across the spectrum of HF. Although initial trials suggested no advantage for a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 106 publications
0
14
0
Order By: Relevance
“…In the previous study, however, these parameters were less severe in patients with NDLVC–REF than in those with DCM. Both AF and elevated LV filling pressure are known clinical risk factors associated with cardiac events in patients with HF 16,17 . This makes the risk of cardiac events in patients with NDLVC–REF comparable with those with DCM in the current study.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In the previous study, however, these parameters were less severe in patients with NDLVC–REF than in those with DCM. Both AF and elevated LV filling pressure are known clinical risk factors associated with cardiac events in patients with HF 16,17 . This makes the risk of cardiac events in patients with NDLVC–REF comparable with those with DCM in the current study.…”
Section: Discussionmentioning
confidence: 67%
“…Both AF and elevated LV filling pressure are known clinical risk factors associated with cardiac events in patients with HF. 16,17 This makes the risk of cardiac events in patients with NDLVC-REF comparable with those with DCM in the current study.…”
Section: Characteristics and Outcomes In Non-dilated Left Ventricular...mentioning
confidence: 67%
“…[77][78][79] The use of SGLT2i has also been associated with reduced incident AF, which may, in part, be due to the reduction in epicardial fat. 80,81 The diuretic effect of SGLT2i may facilitate a reduction in plasma volume and mechanistic studies have shown that they also promote ventricular mass regression, which may cumulatively decrease pericardial restraint. 77,82,83 Likely, in part, through these mechanisms, SGLT2i have demonstrated haemodynamic benefits on PCWP at rest and exercise in systolic heart failure and HFpEF (NCT04730947).…”
Section: Is Eat Merely a Marker Of Functionally Severe Obesity In Hfpef?mentioning
confidence: 99%
“…It is associated with higher rates of stroke, heart failure (HF), hospital admissions, and mortality, thus representing an important medical challenge ( 4 ). Common conditions such as ischemic heart disease and HF with either reduced ejection fraction (EF) or preserved EF (HFrEF and HFpEF, respectively) are important etiological factors for AF ( 5 , 6 ), and they converge together with additional etiological factors such as hypertension, obesity, diabetes mellitus, and sleep apnea to increase the risk of AF in ways that remain elusive ( 7 ). AF is a progressive condition that results in a greater risk of recurrence and persistence over time, complicating treatment efforts ( 8 ).…”
Section: Introductionmentioning
confidence: 99%